Propilar Application For Drug Distribution Solutions For HIV / AIDS Patients - Naftalita Calista Putri; Ridwan Sanjaya; Hendra Prasetya (Journal of Business and Technology, 2021)
The HIV (Human Immunodeficiency Virus) virus is already known to be one of the deadly and very dangerous viruses. This virus attacks white blood cells so that the human immune system decreases and sufferers become susceptible to other diseases and experience complications.[1] Various symptoms that arise as a result of the HIV virus are called Acquired Immunodeficiency Syndrome (AIDS).[1] In Indonesia, the HIV virus case has become a concern of the government because of its increasing development.This HIV virus cannot be removed but can be suppressed by using antiretroviral drugs. Antiretroviral drugs work by suppressing the development of the virus until it reaches its lowest point so that the patient's immune system can function optimally. HIV / AIDS sufferers are required to take this medicine every day and should not be forgotten. Compliance with HIV/AIDS patients or commonly called ODHA is very important for the success of treatment.[2]In carrying out antiretroviral therapy treatment failure often occurs. This is caused by many factors that affect one of them sufferers often forget to take the medicine on time so that treatment fails.For this reason, the report will discuss the design of health applications as a reminder for HIV patients in taking antiretroviral drugs. Besides this application will help antiretroviral drugs better known to the wider community.